Demystifying Globalization
X, 197 p.
Keywords: Globalization, within academic, political and business circles alike, conjures an ever growing diversity of associations, connotations and attendant mythologies. In this volume a distinguished array of international academics assess the contribution of the globalization thesis, in its various guises, to our understanding of social, political and economic change in contemporary societies. They expose, challenge and demystify many of the exaggerated and overgeneralized claims made about globalization, whilst developing a distinctive 'third wave' perspective on the world we inhabit and the processes currently reconfiguring it.